Small polaron hopping conduction in ternary semiconducting CoO-NiO-P2O5 glasses - Rahim, A.S.; Majid, Siti Rohana; Tawati, D.M. (2011)
Five bulk samples of ternary semiconducting CoO-NiO-P2O5 were prepared by press quenching method from the glass melt. The small polaron conduction mechanism of these glasses at temperatures ranging from room temperature to 530 K was discussed based on the results of previous works. The condition for the formation of small polaron hopping in the adiabatic regime at T>theta(D)/2 (where theta(D) is the Debye temperature) can be explained in terms of the polaron bandwidth J.